Socioeconomic Inequality in Gumatdang and Christian Response by Turning Point Development Program Inc - Shitabayashi, Haruka (Asian Journal of Pentecostal Studies, 2022)
The article looks at how one local Christian NGO known as Turning Point Ministries (TPM) in Itogon, Benquet, Philippines, is holistically addressing practical socioeconomic issues. It mentions elites are usually aligned with the global economic order; and also mentions variety of ethnic groups is another factor in forming social structure in the Philippines.